IMPLEMENTASI PROGRAM KELUARGA SEHAT PADA PUSKESMAS WALI KECAMATAN BINONGKO KABUPATEN WAKATOBI - Suriyani BB; La Manguntara; Ewi (Journal Publicuho, 2023)
The research of this research is (1) to find out the implementation of the healthy family program at the Wali health center of the Binongko sub-district, Wakatobi District (2) to find out the factors that hinder the Implementation of the healthy family Program in the Wali public health center, Binongko sub-District, Wakatobi District. The method used in this study is a qualitative descriptive research method by means of interviews and documentation. The results of this study indicate that the implementation of the Healthy Family Program Indicator at the Wali Health Center in Binongko District has been carried out well, although not optimally. Public knowledge about the implementation of this program has begun to change. However, after that, the puskesmas officers did not neglect to continue to provide counseling about the importance of this program. Meanwhile, the obstacles to the implementation of the Healthy Family Program at the Wali Health Center in Binongko District have not been maximized. The factors that support the implementation of the communication factor have been going well with the socialization both internally and externally. While the inhibiting factors from the resource side are the limited facilities of the implementation infrastructure and the delayed disbursement of the budget. From bureaucracy structure factor has not yet established tiered coordination between the health offices and puskesmas.